Silver Nanoparticles Synthesized by Three Species of Genus Streptococcus and Evaluate Their Synergistic Effects with the Oil Extracted from Syzygium aromaticum on Some Clinical Bacterial Isolates - Ahmed, Suaad Ali; Hasan, Hussam Mahmood (Iraqi Journal of Science, 2023)
The nanoparticles biosynthesis is disclosing a new route of exploration concerned with nanotechnology. Silver nanoparticles (AgNPs) are integrated in familiar techniques via chemical routs, for having utterly toxic natures.  Syzygium aromaticum is an aromatic plant which belongs to the genus Eugenia. Three species of the genus Streptococcus were tested using LB for their ability to produce AgNPs and all of them had a brown appearance that confirmed their involvement in AgNPs production. AgNPs were estimated by utilizing a spectrophotometer. The antimicrobial enterprise (AgNPs) of the three species was tested against several types of dangerous bacteria. To determine the MIC, three separate concentrations (v/v) of 0.5%, 5% and 10% of clove oil with dimethyl sulfoxide (DMSO) were prepared (well diffusion technique). Clove oil extract together with AgNPs biosynthesized from three kinds of Streptococcus, were shown to have antimicrobial effects on unusual clinical microorganisms.